2012
DOI: 10.1080/00140139.2012.706715
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical and subjective assessment and comparison of three ambulance cot design configurations

Abstract: Effects of ambulance cot design features (handle design and leg folding mechanism) were evaluated. Experienced ambulance workers performed tasks simulating loading and unloading a cot to and from an ambulance, and a cot raising task. Muscle activity, ratings of perceived exertion, and performance style were significantly affected by cot condition (p < 0.05). Erector Spinae activity was significantly less when using Cot-2's stretcher-style handles. Shoulder muscle activity was significantly less when using Cot-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…Use of Cot A, which had an independent system, resulted in significantly lower muscle activity and external forces experienced by the participants, for the two tasks and three levels of patient weight experienced in this study relative to Cot B. These findings are consistent with those of Kluth and Strasser (2006) and Sommerich et al (2012) who reported on the independent operation of front and rear cot wheels during the loading and unloading of non-powered ambulance cots.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Use of Cot A, which had an independent system, resulted in significantly lower muscle activity and external forces experienced by the participants, for the two tasks and three levels of patient weight experienced in this study relative to Cot B. These findings are consistent with those of Kluth and Strasser (2006) and Sommerich et al (2012) who reported on the independent operation of front and rear cot wheels during the loading and unloading of non-powered ambulance cots.…”
Section: Discussionsupporting
confidence: 94%
“…Muscle activity levels reported in the current study are generally lower than values reported in the manual cot studies of Kluth and Strasser (2006) and Sommerich et al (2012). This may, in part, reflect a benefit of the powered retraction (folding) of the legs in the current study in contrast to the contribution required from the operator's effort to the leg folding of the manual cots.…”
Section: Discussioncontrasting
confidence: 79%
“…Muscle activity was recorded using a multi-channel EMG system (Delsys, Boston MA). Electrode locations and site preparation were standardized for this study and are described in detail in Sommerich et al (2012). The data were collected at 1200 Hz using the Motion Monitor data acquisition system (Innsport, Chicago IL).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have begun to investigate ways to reduce the occurrence of these injuries. In general, the approaches focus on 1) attempting to improve the physical capacity of EMS workers (Aasa et al 2008), 2) reducing the physical stress imposed by manual patient transfer and carry tasks (Lavender et al 2007a, Lavender et al 2007b, and 3) exploring different designs of non-powered ambulance cots and/or their loading systems (Kluth and Strasser 2006, Cooper and Ghassemieh 2007, Sommerich et al 2012. The latter two approaches have shown that physical stress imposed on operators can be altered by design modifications to equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003 Hignett et al reported a systematic literature review on patient handling activities across healthcare sectors including three studies of moderate quality which found that ambulance work can result in harmful working postures (in particular over reaching/over stretching), with the highest risk tasks involving transportation of patients (Doormal et al, 1995;Furber et al, 1997;Massad et al, 2000). Several studies have investigated these risks in terms of stretcher loading and design (Jones and Hignett, 2007;Sommerich et al, 2012), working environment (Ferreira and Hignett, 2005;Hignett et al, 2009a&b), and equipment design for carry chairs (Ferreira and Stanley, 2005), including vertical stair descent (Lavender et al, 2015).…”
Section: Manual Handling Risksmentioning
confidence: 99%